The impact of parents' perceptions of the double reduction policy on educational anxiety: parental involvement as a mediator and gender as a moderator - Sulong, Rose Manisah; Che Hassan, Norlizah; Zhang, Shuyang (Taylor & Francis, 2024)
In China, educational involution has been escalating, increasing pressure and anxiety on students and their parents. In the pursuit of higher academic achievements, many families invest substantial resources, while profit-driven tutoring institutions have disrupted the essence of education. To address this challenge, the Chinese government introduced the double reduction policy three years ago, aiming to alleviate students' extracurricular burdens and encourage societal oversight of the policy's implementation. Three years later, researchers surveyed 296 parents to explore their perceptions of the double reduction policy, the state of educational anxiety, and their involvement levels. The findings revealed that higher parental educational anxiety correlated with a stronger perception of the policy. Moreover, active parental involvement significantly mediated the reduction of educational anxiety, highlighting the importance of family support. Gender factors also moderated these relationships.This study appreciates the wisdom of the policymakers behind the double reduction policy while emphasizing the need for flexibility to adapt to the rapidly changing educational landscape, ultimately helping families find balance and peace amid ongoing reforms.